Perjalanan Wanita Pekerja Seks Komersial (PSK): Sebuah Kebebasan, Pembuktian Diri, dan Cinta - Pujhana, I Kadek Wahyu; Tobing, David Hizkia (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 3 (2021): Volume 1 Nomor 3 Tahun 2021 - Widya CakraDO - 10.24843/widyacakra.2021.v1.i3.p73137, 2022)
Working as a sex worker is a job that is in constant difficulty. The bad stigma in society, the social status that prohibits the existence of this work, to the legal, religious, and cultural social order in Indonesia also prohibits this work. Previous research has reported that earning money quickly is a major factor in maintaining and expanding the presence of prostitution locations in a number of settings. Apart from economic factors, a sex worker is actually someone who is the same as other people who also have emotional feelings when working. It is important then that there is a study that is able to describe the journey of sex workers to enter and survive in prostitution. This research is a phenomenological qualitative study, with semi-structured online and offline interviews, and observations on social media among five sex workers in Bali. The data were then analyzed by theoretical coding by Strauss & Corbin (1990). The results of the research show that working sex has provided freedom, a place to prove oneself, and find love. These three findings prove that prostitution is not only a sexual world to get money, but a sexual world to get the same emotional satisfaction. This study provides an understanding of the journey of sex workers, and their contribution to psychosocial aspects in the world of prostitution.